2010
DOI: 10.1111/j.1532-5415.2010.02882.x
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Year Effects of Interdisciplinary Intervention for Hip Fracture in Older Taiwanese

Abstract: The interdisciplinary intervention for hip fracture benefited elderly persons with hip fracture by improving clinical outcomes, self-care ability, and physical health-related outcomes and by decreasing depressive symptoms during the first 24 months after hospital discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
95
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 27 publications
3
95
0
Order By: Relevance
“…Some of the trials included longer follow-up periods after the intervention, but when the effects of the intervention were compared to those of usual care during the intervention period, four studies found better mobility results after the intervention. Latham et al (20014) reported better results in the Short Physical Performance Battery and functional balance, Orvig et al (2011) higher physical activity, Shyu et al (2010) increased quadriceps strength and walking ability, Tinetti et al (1999) better upper extremity strength, and Crotty et al (2002) less fear of falling for the intervention group than for the usual care group. Nevertheless a need for further studies of home-based rehabilitation programs among hip fracture patients is widely acknowledged (Handoll et al 2009, Handoll, Sherrington & Mak 2011, Ftouh et al 2011, Donohue et al 2013.…”
Section: Rehabilitation After Hip Fracturementioning
confidence: 99%
See 4 more Smart Citations
“…Some of the trials included longer follow-up periods after the intervention, but when the effects of the intervention were compared to those of usual care during the intervention period, four studies found better mobility results after the intervention. Latham et al (20014) reported better results in the Short Physical Performance Battery and functional balance, Orvig et al (2011) higher physical activity, Shyu et al (2010) increased quadriceps strength and walking ability, Tinetti et al (1999) better upper extremity strength, and Crotty et al (2002) less fear of falling for the intervention group than for the usual care group. Nevertheless a need for further studies of home-based rehabilitation programs among hip fracture patients is widely acknowledged (Handoll et al 2009, Handoll, Sherrington & Mak 2011, Ftouh et al 2011, Donohue et al 2013.…”
Section: Rehabilitation After Hip Fracturementioning
confidence: 99%
“…Ten previously published multi-component home-based rehabilitation studies after a hip fracture, which investigated the effects of rehabilitation on mobility recovery compared to usual care, were found (Crotty et al 2002, Crotty et al 2003, Latham et al 2014, Shyu et al 2010, Tseng, Shyu & Liang 2012, Tinetti et al 1999, Ziden, Frandin & Kreuter 2008, Ziden, Kreuter & Frandin 2010. The studies include seven different trials, and from those, three trials included two separate papers.…”
Section: Rehabilitation After Hip Fracturementioning
confidence: 99%
See 3 more Smart Citations